Water Scarcity: Day Zero in the UNEVE Community - Strengthening a Water Culture - González Hernández, José de Jesús; Fierro Rosales, Laura; Vázquez Ibarra, Irene; López Espinosa, Irma (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To promote and raise awareness within the student community about water culture to delay the arrival of Day Zero and thereby contribute to the recommendations outlined in the Sustainable Development Goals (SDGs). MATERIAL AND METHOD: This research was conducted using a quantitative approach with an exploratory scope. It focuses on an issue that has not yet been addressed in the context, and its results will serve as a precedent for broader and more in-depth studies. The population studied includes administrative staff, faculty, and students from the Humanities-Business undergraduate program. RESULTS: The findings highlight the urgent need for environmental education focused on water culture. It is imperative for the university community to strengthen strategies and implement actions to mitigate the problem. CONCLUSIONS: Updating academic programs within educational institutions presents an opportunity to incorporate content that encourages reflection on Day Zero and the importance of a water culture.